Effectiveness of Combination Therapy of Stereotactic Body Radiation Therapy with Lenvatinib in Advanced Hepatocellular Carcinoma - Alifia Sabira Putri; Rovera Nuriasti; Balqis Prudena Kurnia Pambudi; Naufal Revaldy Fauzan; Baiq Zaskia Maudina; Yoga Prawira; Anak Agung Ayu Regina Larasati; Catarina Budyono (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy)
Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer and has a high mortality rate, especially in advanced stages. Treatment of advanced HCC remains a significant challenge due to limited effective therapeutic options. This study examines the effectiveness of combining Stereotactic Body Radiation Therapy (SBRT) and Lenvatinib in advanced HCC patients. SBRT is a high-precision radiation technique that allows high-dose irradiation of tumor targets with minimal damage to surrounding healthy tissues. At the same time, Lenvatinib is a multikinase inhibitor that inhibits several critical molecular pathways in angiogenesis and tumor cell proliferation. The results showed that the combination of SBRT and Lenvatinib significantly improved overall survival (OS) by reducing the risk of death by 63%, progression-free survival (PFS) reduced the risk of tumor progression by 67%, intrahepatic tumor progression-free survival (IHPFS) showed a decrease of 71%, objective remission rate (ORR) was also higher in the combination group (56.8%), and disease control rate (DCR) of 91.9% which was higher than the use of Lenvatinib alone. However, this combination therapy also carries a higher risk of side effects, including hypertension and diarrhea, which require close monitoring and dose adjustment. This study suggests combining SBRT and Lenvatinib may be a more practical approach to treating advanced HCC. However, the treatment strategy needs to be tailored to the patient's condition to minimize the risk of toxicity.